Bukan Korban, tetapi Rizom: Koreografi Ketahanan Tubuh Migran di Reruntuhan Kapitalisme Taiwan - Listyorini, Anastasia Melati (Retorik: Jurnal Ilmu Humaniora, 2025)
This article challenges dominant narratives that position Indonesian migrant workers in Taiwan as passive victims of global capitalism. Drawing on a three-year performative ethnography (2022–2024) combined with critical digital content analysis, the study develops the concept of choreographies of resilience to examine how migrant bodies claim space, time, and meaning under highly restrictive living conditions. The analysis focuses on two interrelated everyday practices: the transformation of cramped dormitory rooms into virtual stages, and the phenomenon of sholawat dance as an expression of kinesthetic piety. By framing Taiwan as a landscape of “capitalist ruins” (Anna Tsing), the study demonstrates that these practices enact forms of agency that are not necessarily resistive, but instead operate through the creative inhabitation of norms (Saba Mahmood) and bodily performativity (Judith Butler). The findings show that digital choreographic practices function both as survival tactics (Michel de Certeau) and as a politics of visibility. Platforms such as TikTok operate as ambivalent contact zones (Mary Louise Pratt): while embedded within the logics of platform capitalism (Nick Srnicek), they nevertheless enable the formation of collective bodily archives, affective networks, and alternative cultural spaces. The study argues that migrant bodily resilience is contextual, embodied, and rooted in everyday practice.